2004
DOI: 10.1038/sj.gt.3302331
|View full text |Cite
|
Sign up to set email alerts
|

Bioluminescence imaging reveals a significant role for complement in liver transduction following intravenous delivery of adenovirus

Abstract: The effect of complement on transgene expression was evaluated in vivo and in vitro using mice lacking complement components. Complement component 3 (C3) deficient mice (C3 À/À) and appropriate wild-type controls were intravenously injected with a replication incompetent, luciferaseexpressing normal Ad5 (Ad5Luc1), or fibritin-fiber Ad5 (Ad5FFLuc1). Repeated, noninvasive bioluminescence imaging was conducted over 35 days. Our data show for the first time that C3 facilitates both short-and long-term hepatic expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…Our studies and others illustrate the importance of considering serum factors in evaluation of Ad vector tropism and receptor interactions (23,29,37). These findings provide an explanation for the numerous studies that demonstrate the similar distribution and inflammatory properties of systemically administered wildtype and tropism-modified Ad vectors that are based on the traditional CAR/integrin paradigm (1,20,22).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Our studies and others illustrate the importance of considering serum factors in evaluation of Ad vector tropism and receptor interactions (23,29,37). These findings provide an explanation for the numerous studies that demonstrate the similar distribution and inflammatory properties of systemically administered wildtype and tropism-modified Ad vectors that are based on the traditional CAR/integrin paradigm (1,20,22).…”
Section: Discussionmentioning
confidence: 67%
“…The finding of RGD-dependent cellular interactions uncovered in the absence of liver resident macrophages (Kupffer cells) suggests that adenovirus-leukocyte interactions occur independent of the traditional paradigm involving CAR and integrins (20). Recently, several studies have demonstrated opsonization of Ad vectors in vivo that play a significant role in vector tropism (29,37). The adenovirus capsid binds to and activates proteins in the classical and alternative complement pathways, including C3 and C4BP (5,14,29).…”
mentioning
confidence: 99%
“…One issue with using human material is that individual humans have variable levels of specific anti-Ad antibodies that activate complement via the classical pathway (9). For mice, in vivo studies have shown that complement component C3 enhances liver transduction by Ad and also augments the cyto- kine response to Ad (26,70). In vitro, the isolated Ad5 fiber knob can bind mouse complement proteins C3, C4, and C4-binding protein (45), but it is not clear whether this binding is direct or indirect; nor is it apparent which of the complement activation pathways may be involved.…”
Section: Resultsmentioning
confidence: 99%
“…A fuller understanding of these interactions is necessary for the development of safe and efficient targeting to individual organs. Prior studies have demonstrated Ad interactions with red blood cells (2,12) and white blood cells (9), as well as plasma proteins such as coagulation zymogens and complement pathway components (15,18,23). Recent evidence has shown a substantial role for coagulation zymogens in the delivery of Ad to the liver following intravascular injection (15,18).…”
mentioning
confidence: 99%